Wedding Tourism and India - Suklabaidya, Paramita (Atna Journal of Tourism Studies, 2008)
Wedding Tourism — a seemingly new form of Tourism is causing a lot of excitement in the tourism industry. In some cases it is also referred to as "Marriage Tourism" or "Destination Wedding". Whatever maybe the way one addresses this phenomenon, it is for sure that we cannot ignore this new trend in the tourism sector. According to the bridal magazine, Conde Nast Bridal Group's survey, globally wedding tourism has seen a growth of 400% in the past 10 years. Globalisation and a growing interest in each other's culture is probably one of the primary reasons for this trend. The people world over are attracted to say their "I Do" in some unique way or at an exotic location. Europe based couples are known to fly overseas to destinations like Las Vegas, Hawaii, the Caribbean and Cyprus in order to marry. No wonder these destinations rank among the favourites. India as a country is one of the beneficiaries of this new trend. Both NRIs and foreigners are choosing an Indian wedding, with all its traditional rituals and interesting locales. The already booming Indian wedding industry, with a revenue of Rs.50, 000 /- crore per annum and a growth rate of 25% per year is looking for ways to tie up with leading hotels and travel agents to woo this growing tourist segment. Although, in India, it is difficult to come across the exact statistics and figures regarding this tourism sector, nevertheless we cannot ignore this segment. This paper is an attempt to understand this concept of wedding tourism. The paper also examines the possible reasons for its growing popularity and its role in creating other business avenues for the travel and hospitality and allied industries, such as wedding resorts and others. The scope of wedding tourism in India is also explored.